FUNCTIONAL REQUIREMENTS FOR INFORMATION SYSTEM OF INTERMODAL TRANSPORT TERMINALS - Hrudkay, Karol (Doprava a spoje, 2012)
The paper deals with the intermodal transport terminals (ITT) from point of view of the defining of the requirements for the functionalities of its information systems. The contribution begins by describing the concept of intermodal transport in Slovakia. The modular solution of the ITT information system is mentioned. The core of the article is devoted to detailed description of the functions of the particular modules of the information system of ITT.